Red blood cell variables and correlations with body mass components in boys aged 10-17 years - Gligoroska, Jasmina Pluncevic; Gontarev, Serjoza; Maleska, Vesela; Efremova, Ljudmila; Stojmanova, Daniela Shukova; Manchevska, Sanja (The Turkish Journal of Pediatrics, 2020)
The objective of this study was to analyze the hematologic parameters and their correlation with body composition components in healthy boys at pubertal age. One hundred and ninety physically active male subjects, aged 10 to 17 years, mean age 13.87 ±4.5 years, were included in the study. Capillary blood was drawn from all subjects and the following hematologic parameters were measured: RBC, Hct, Hb, MCV, MCH, MCHC. The following body components derived from Matiegka anthropometric method were assessed: muscle mass (MM), bone mass (BM), and body fat mass (BF). The mean values (±SD) of hematologic parameters were: RBC= 4.87±0.41 x 10 < sup > 12 < /sup > /L, Hb=14.24±1.24 g/dL, Hct=43.83±3.8%. Anthropometric characteristics were as follows: body mass index (BMI) = 20.26± 3.27 kg/m < sup > 2 < /sup > , relative muscle mass (MM%) = 53.18± 3.19%, bone mass (BM%) = 18.83± 2.4% and body fat percentage (BF%) = 15.19± 2.64%. Correlation analysis between hematologic parameters and body composition showed a moderate to strong correlation between RBC, Hb and Hct and all body components. The strongest correlations were found between Hb and Hct, and muscle mass (r= 0.60; r= 0.61) and lean body mass (r= 0.59). The body fat mass showed also a positive association with RBC (r=0.47); Hb (r=0.47) and Hct (r=0.48). Our findings showed that the relationship between anthropometric measures and RBC variables in healthy physically active boys were positively correlated, but the level of association was higher with skeletal muscle mass.